Designing a Microstrip coupled line bandpass filter - Ragani, Taoufik; Touhami, N. Amar; Agoutane, M. (International Journal of Engineering and Technology, 2013)
Bandpass filters play a significant role in wireless communication systems. Transmitted and received signals have to be filtered at a certain center frequency with a specific bandwidth, in this paper, a coupled-line bandpass Filter at the center frequency 6 GHz with the wide bandwidth of 2 GHz. this type of filter can be used in WLAN and other applications for the frequency range of 5-7 GHz.